LETTERS LEARNING JAPANESE APPLICATIONS WITH VISUAL BASIC 6.0 Hiragana - Elly Agustina Julisawati (JAKSTIK Journal, 2006)
The application development is very interesting to discuss, in making writer application form to make kode_user, datagrid, text input on the Indonesia-Japan text, animated images run and display the letters in the image. In carrying out this application to join the first user identity is registered in the program, if the user has registered the user can type the user should code in the text the user code then the cursor will automatically direct text input in Indonesia, from where you can langgsung use this application to enter word of the Indonesian-Japanese. If you want to know the result of user input should click the enter button and if the user wants to display the hiragana letter based on the input then the user can click the letters appear. In this study, the authors restrict language learning hiragana which includes members of the human body that are stored in a database using Microsoft Office Access 2003. This application is designed with the view that attention to simplicity in pengoprasiannya.Â